Peran Algoritma Julia Set Dalam Mengkonstruksi Pembelahan Sel Mitosis - Faridatul Masruroh; Esty Saraswati Nurhatiningrum (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2016)
Fractal geometry is a structure that is constructed of an element geometry (points, lines, areas, and space) and these elements are experiencing faults equation is not continuous, monotonous go up or down the course, the graph circular, blending and converging to the center, and size scale in each substructure same. This is similar to the principle of cell division, mitosis is the process of cell division that splits into two cells, and each cell has the same chromosomes as their parent. Mitosis is usually followed by cytokinesis, the division of the cytoplasm to two identical daughter cells. The stages of mitotic division consists of prophase, metafese, anaphase, telophase and interphase. Of the five stages only obtained three stages which can be searched equation through the Julia set algorithm, namely prophase, telophase, and interphase. The mathematical equation for prophase and interphase are the same, namely , the difference is the position x. At prophase position x is -0,9 ? x ? 0,1 while at the interphase stage position x is -0,9 ? x ? 0,9. The mathematical equation for telophase stage is .